1991
DOI: 10.1111/j.1365-2958.1991.tb02160.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of starch‐ and Lambda‐receptor sites in maltoporin: identification of substitutions causing direct and indirect effects on binding sites by cysteine mutagenesis

Abstract: Cysteine mutagenesis was used to test the proximity of 16 residues to protein-ligand interaction sites in maltoporin (LamB protein). LamB protein with additional cysteines was incorporated into the outer membrane of Escherichia coli except with a Ser-30----Cys substitution. Phage Lambda and starch binding was assayed before and after incubation of mutants with six thiol-specific reagents. Four categories of mutation were recognized on the basis of phenotype and modification for each of the Lambda- and starch b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…1) (4), which suggested that these residues constitute a membrane-external loop. It has previously been demonstrated that a Ser-57--3Cys mutant had phenotypes no different from those of the wild type (12), which is also consistent with the tolerance of these residues in accepting neutral substitutions. However, labeling studies on the mutant carrying the Ser-57--*Cys mutation showed that the thiol was not as accessible as expected for a freely external loop (11).…”
Section: Resultssupporting
confidence: 60%
“…1) (4), which suggested that these residues constitute a membrane-external loop. It has previously been demonstrated that a Ser-57--3Cys mutant had phenotypes no different from those of the wild type (12), which is also consistent with the tolerance of these residues in accepting neutral substitutions. However, labeling studies on the mutant carrying the Ser-57--*Cys mutation showed that the thiol was not as accessible as expected for a freely external loop (11).…”
Section: Resultssupporting
confidence: 60%
“…Neither the sucrose porin ScrY nor the nonspecific E. coli porins conserve these residues to the extent found in OprB, suggesting a possible role in binding maltodextrins; a characteristic common to both OprB and LamB. Residue W74 in LamB and conserved in OprB and ScrY as W71 and W151, respectively, has also been specifically linked to maltodextrin binding (Charbit et al, 1988;Francis et al, 1991), suggesting some of the conserved residues within this region are involved in the formation of a binding site. Further studies of these residues within OprB and LamB are warranted to compare and contrast the effects on the structure and function of each of these porins.…”
Section: Discussionmentioning
confidence: 99%
“…Enhanced uptake of starch breakdown products through the LamB channel is likely to give the enteric bacteria a competitive advantage. A large assortment of lamB mutants has been used to probe the roles of different parts of the protein [7, 8, 9]. Once the x-ray structure provided details of its β-barrel topology and the residues lining the “greasy slide” that confer specificity to the pore [10, 11, 12], genetic analysis of the architecture of LamB protein could be targeted to determining structure-function relationships of various loops and pore residues [13, 14].…”
Section: Introductionmentioning
confidence: 99%